A bilinear constitutive response for polyureas as a function of temperature, strain rate and pressure. Issue 35 (19th May 2017) - Zhang, Xiaoqiong; Wang, Jianjun; Guo, Weiguo; Zou, Ruilu
ABSTRACT: Polyurea is widely applied as a coating material to increase the survivability of structures under impact loading. In this study, a systematic experimental program about the stress–strain behaviors of two polyaspartic esters polyureas is conducted over the temperature range of 233 K–293 K and strain rate range of 0.001/s–15, 000/s, including the high‐pressure effects on the response of the polyureas. Based on the experimental results, the effects of temperature, strain rate, and pressure on the stress–strain behaviors are analyzed, the mechanical properties of the two polyureas are compared. The temperature and strain rate dependences of the Young's modulus, yield stress, and strain hardening slope are modeled. Finally, a bilinear constitutive model is proposed to describe the temperature, strain rate, and pressure dependences of the stress–strain behaviors. The model predictions, which agree well with the experimental results, provide basis for the application of the two polyureas. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45256. Abstract :